(untitled) (American International Journal of Sciences and Engineering Research, 2022)
Bangladesh is one of the top brick manufacturing countries in the globe. With rapid urbanization and industrialization, the brick manufacturing industry is elevating to its peak level day by day and contributing to the country’s GDP significantly. This research aims to investigate the current environmental and health threat coming from brick kilns around the capital of Bangladesh. The selected areas are Savar, Tongi, Amin Bazar and Ashulia. The methodology followed in this study was field surveying in the selected areas and information acquisitions from the secondary data. Results from this study revealed that brick kilns are highly responsible for environmental pollution that subsequently deteriorates the air quality, causes land degradation, threatens biodiversity and poses a potential impact on human health. Results also revealed that there are mainly four types of brick kilns found in selected areas e.g. Chimney Kiln (CK), Zigzag kiln (ZK), Hoffman Kiln (HK) and Hybrid Hoffman Kiln (HHK). Of these, the Fixed Chimney Kiln is found to be very obsolete at present days and creates environmental pollution at different levels. Besides these, strict implementation of the Brick Manufacturing and Brick Kilns Establishment (Control) Act, 2013 in the studied locations is still far away. This paper urges the attention of the policymakers as well as the researchers to prioritize the solution to this promising but ever-increasing pollution-causing industry of Bangladesh in sustainable ways. JEL Classification Codes: Q53, Q54, Q58, R11.